Study of Formulation of Soybean (Glycine max L.) Milk and Purple Sweet Potato (Ipomoea batatas Poir) Crude Extract in The Making of Non-Dairy Ice Cream - Eva Mayasari; Megawati Meme; Suko Priyono (International Journal of Advance Tropical Food, 2021)
Soybean milk and purple sweet potato are used as the main ingredients in the making of non-dairy ice cream. This study aims to determine the best characteristics of non-dairy ice cream from the formulation of soybean milk and purple sweet potato crude extract. The research design used a completely randomized design with one-factor treatment and four replications and was analyzed statistically with the F test Analysis of Variance at 5% level. The treatment in this study was the formulation of soybean milk and purple sweet potato extract consisting of 60%:0%; 52%:8%; 44%:16%; 36%:24%; 28%:32% of the total ice cream dough. The parameters observed were fat content, protein content, total solids, overrun, melting time, and hedonic sensory evaluation (appearance, texture, taste, and odor). Based on the Indonesian National Standard for ice cream 01-3713-1995 qualified showed that the formulation of soybean milk and purple sweet potato extract crude extract 52%:8% was the best treatment with 9.83% fat content, 2.89% protein content, 34.15% total solids, 49.26% overrun, 13.12 minutes melting time, and hedonic scale for appearance 6.76 (like extremely), texture 5.32 (like), taste 5.58 (like very much), odor 5.56 (like very much). The formulation soybean milk and purple sweet potato crude extract are effects of physicochemical properties and sensory evaluation of non-dairy ice cream.